Official Status As a Tool of Language Revival? A Study of the Language Laws in Russia’s Finno-Ugric Republics - Konstantin Zamyatin (Journal of Ethnology and Folkloristics)
This study explores the legal and institutional position of Finno-Ugric languages according to the language laws of the national republics in post-Soviet Russia. The aim is to understand whether the republican authorities intended to use the official designation of state language as a policy device with which to ensure the revival of titular languages. The approach of the study is to test revivalist theories that establish a link between official status and language revival by comparing the number of institutionalised elements of official status in the republics. For the purpose of comparison, the study focuses on education and work environment among the domains within the public sphere of language use. The results demonstrate that the framing of official status in these sectors provided only some additional opportunities for the expansion of language use, while the extent of their institutionalisation directly correlated with the level of political representation of ethnic elites.